2018
DOI: 10.1002/2017ef000710
|View full text |Cite
|
Sign up to set email alerts
|

Climate Impacts in Europe Under +1.5°C Global Warming

Abstract: The Paris Agreement of the United Nations Framework Convention on Climate Change aims not only at avoiding +2°C warming (and even limit the temperature increase further to +1.5°C), but also sets long‐term goals to guide mitigation. Therefore, the best available science is required to inform policymakers on the importance of and the adaptation needs in a +1.5°C warmer world. Seven research institutes from Europe and Turkey integrated their competencies to provide a cross‐sectoral assessment of the potential imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
90
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(116 citation statements)
references
References 41 publications
10
90
0
3
Order By: Relevance
“…The increasing trends of the air temperature (T) are similar for Kaunas and Sarajevo WS, ranging from 0.052 0 C to 0.047 0 C. Increasing trends ware also detected for the annual amount of precipitation, ranging from 3.582 mm year -1 in Kaunas to 1.724 mm year -1 in Sarajevo, Annual sum of precipitation has increased by more than 100 mm in Kaunas for a period of 30 years . The observed air temperature and precipitation change patterns in Lithuania and B&H are consistent with the predominant trends in other areas of East Europe Bukantis ArūNas & Rimkus Egidijus, 2005;Jaagus et al, 2009;Branković et al, 2013;Burić et al, 2013;Tripolskaja & Pirogovskaja, 2013;Unkasevic & Tosic, 2013;Rutgersson et al, 2014) and with trends observed globally (Kharin et al, 2013;Trenberth et al, 2013;Jacob et al, 2018;Popov et al, 2018).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The increasing trends of the air temperature (T) are similar for Kaunas and Sarajevo WS, ranging from 0.052 0 C to 0.047 0 C. Increasing trends ware also detected for the annual amount of precipitation, ranging from 3.582 mm year -1 in Kaunas to 1.724 mm year -1 in Sarajevo, Annual sum of precipitation has increased by more than 100 mm in Kaunas for a period of 30 years . The observed air temperature and precipitation change patterns in Lithuania and B&H are consistent with the predominant trends in other areas of East Europe Bukantis ArūNas & Rimkus Egidijus, 2005;Jaagus et al, 2009;Branković et al, 2013;Burić et al, 2013;Tripolskaja & Pirogovskaja, 2013;Unkasevic & Tosic, 2013;Rutgersson et al, 2014) and with trends observed globally (Kharin et al, 2013;Trenberth et al, 2013;Jacob et al, 2018;Popov et al, 2018).…”
Section: Resultssupporting
confidence: 84%
“…This indicates that the consequences of climate change are predominantly, but not exclusively negative and dependent on geographical location. Climate change may have a positive effect on the yield and quality of winter crops due to the extended growing period in northern Europe (Radusin et al, 2016;Jacob et al, 2018). However, the rest of Europe, especially the Mediterranean region, will mostly be negatively affected (Behrens et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…We stress that a temporary excursions over 1.5 °C above preindustrial conditions would not necessarily constitute an exceedance of the Paris Agreement, which has been interpreted to refer to human‐induced climate change over periods of at 30 years (Rogelj et al, ). Indeed, complying with the Paris Agreement is still achievable (Rogelj et al, ) and important, given the impact of further warming on Arctic Sea Ice (Jahn, ; Niederdrenk & Notz, ; Sigmond et al, ), Greenland, and West Antarctic ice sheets and sea level rise (Rasmussen et al, ), regional climate (Jacob et al, ; M. A. Taylor et al, ), and extremes (Dosio & Fischer, ; Li et al, ). The first temporary excursions above 1.5 °C, if they occur, would not necessarily lead to many of these effects but they would be an important indication of the proximity to the Paris threshold and could generate interest from the media and general public.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 2015 Paris Agreement, a significant body of research has quantified the impact of different levels of warming specified by the various thresholds of global average temperature (e.g. 1.5°C, 2°C, 3°C) (King and Karoly 2017, Wang et al 2017, Jacob et al 2018, Li et al 2018, Sylla et al 2018. However, most of these studies applied the GCM projections with relatively coarse resolution, which is not appropriate for investigating detailed features at the regional to local scales.…”
Section: Introductionmentioning
confidence: 99%